Al-Ghazali’s Unspeakable Doctrine of the Soul: Unveiling the Esoteric Psychology and Eschatology of the Ihya’ by Timothy Gianotti (Leiden: Brill, 2001. 205 pages.) (American Journal of Islam and Society, 2006)
Gianotti’s purpose behind this monograph is to draw out Ghazali’s positionon the vexed question of the true nature of the soul and its state in the afterlife.Ghazali’s actual views on this question have been a point of seriousdebate in both the Muslim intellectual tradition and Ghazali scholarship inthe West. At the heart of this debate lies the question of his true allegiance:Was the man, widely held to be the mujaddid (renewer of religion) of thefifth Islamic century, a full-fledged Asharite, as tradition has made him outto be, or was he, as others have suggested, a closet Avicennian? Or was he,to complicate matters even further, neither? The source of the problem restson the apparently conflicting doctrines he articulated in various places concerningthe soul in various places in his vast and multi-layered literary oeuvre.These seeming inconsistencies led Averroes, in the thirteenth century, toaccuse Ghazali of adhering “to no one doctrine in his books,” and of beinga Sufi with Sufis, an Asharite theologian with the Asharites, and a philosopherwith the philosophers (p. 19).Gianotti confesses that the “tensions and ambiguities are real and begresolution” (p. 8). He poignantly asks, however, whether they were the“unintentional mess left by a brilliant but indisciplined mind,” or whether ...